Structural degradation and permeability evolution of red sandstone under dry-wet cycles in the Baihetan hydropower station reservoir area - Shizhe LIN; Xinli HU; Haiyan ZHANG; Ningjie LI; Xinyu LIU (Zhongguo dizhi zaihai yu fangzhi xuebao)
Influenced by the cyclic fluctuation of reservoir water levels and rainfall, the rocks of reservoir bank slopes have been subjected to alternating wet and dry environments for a long time. This leads to their deterioration and damage, posing a great threat to the stability of the bank slopes. This study investigates the red sandstone of the Baihetan hydropower station as the research object, and the structural deterioration of the red sandstone under wetting-drying cycles of sodium sulfate salt solution were investigated by carrying out wetting-drying cycles test, CT scanning test, digital core modeling and seepage simulation. The results show that the mass loss rate (α) and permeability (k) of the red sandstone increase exponentially with the number of cycles (N). The total porosity, effective porosity, and effective porosity ratio initially decrease and then increase with N. The study suggests that the structural deterioration of the red sandstone under wetting-drying cycles in the salt solution results from the combined effect of dissolution and salt crystallization. In the early stages, structural damage is mainly due to calcite, plagioclase feldspar and other minerals in solution dissolution. In the middle stages, the rocks undergoes damage from both salt crystallization and dissolution. In the later stages, the effect of salt crystallization is gradually weakened and rock dissolution becomes the dominant factor causing rock damage again. The results of the study provide an important theoretical basis for the long-term stability evaluation of reservoir slopes at the Baihetan hydropower station.